Character Education Efforts in Anticipation of the McDonaldization Phenomenon - Pramusinto, Bambang (PPSDP International Journal of Education, 2023)
The purpose of this study is to describe activities to strengthen character education in anticipation of the Mcdonalization phenomenon at SMA Negeri 1 OKI. Researchers conducted interviews, documentation, and observations to collect data. The research method employs descriptive qualitative methods. The negative impact of the McDonaldization phenomenon in the school environment is an attitude of simplifying the process of achieving something, undermining local cultural values, and excessive reliance on technology, which has the potential to erode student confidence in their abilities and must be anticipated with programs to strengthen student character through Civics education and religious education through several extracurricular activity programs. Character education programs implemented in educational institutions have an impact on preventing Mcdonalization at SMA Negeri 1 OKI.